Paediatric tuberculosis: A decade-long experience in a tertiary care centre - Kamath, K Madhava; Giridhar, B H; Philip, Prijo (Indian Journal of Child Health, 2018)
Background: The World Health Organization estimates in 2013 revealed that up to 80,000 children die from tuberculosis (TB) each year and children account for over half a million new cases annually. The incidence of extrapulmonary TB (EPTB) is also on the rise. Aims: To study and note the total pediatric TB cases reported over a decade. Analysis of EPTB at the center was also attempted. Methods: Retrospective analysis of TB cases diagnosed during the past decade was attempted, through information registered in the hospital TB registry. Cases aged <18 years were identified as pediatric TB. Pulmonary TB and EPTB cases were analyzed. Results: All of 289 pediatric TB cases were identified from a total of 1389 TB cases in general. Pediatric TB comprised 20% of the diagnosed. Among these, 176 patients were pulmonary TB, amounting to 60% of all cases of TB. The remaining 113 cases were identified to be that of extrapulmonary TB constituting 40% of the total study populace. Among EPTB, lymph node TB was the most common subtype amounting for 42% of all cases of EPTB. This was followed by skeletal TB (23%), pleural TB (12%), gastrointestinal TB (11.5%), nervous system TB (5%), and cutaneous and genitourinary TB accounted for 2.6% each. Conclusion: Childhood TB is an underdiagnosed entity in India. EPTB is alarmingly on the rise, and clinicians need to be wary of the presentations and pitfalls in diagnosis. Awareness of the same is quintessential.